Usefulness and description of the intestinal bypass technique in children with short bowel syndrome: report of a Mexican cohort - Eustorgio S. García-Cárdenas; Isela Nuñez-Barrera; América L. Miranda-Lora; Juan J. Bolaños-Perez; Rosalinda Lopez-Rodriguez; Norma Briseño-Chavarria; Salvador Villalpando-Carrión (Permanyer, 2024)
Background: Short bowel syndrome (SBS) is one of the most frequent causes of intestinal failure, needing parenteral nutrition to maintain an energy-protein and water-electrolyte balance. At the Hospital Infantil de México Federico Gómez (HIMFG), the formation of two stomas is a technique used for intestinal rehabilitation, where the use of residue through the bypass technique (BT) helps to maintain gastrointestinal functionality, water-electrolyte, and nutritional stability. This study aimed to describe the technique of using intestinal residue through BT as a treatment strategy in intestinal rehabilitation and its effect on the biochemical and nutritional status of pediatric patients with SBS. Methods: An analytical and retrospective cross-sectional study was performed in patients hospitalized at HIMFG with SBS who underwent BT during their hospital stay between 2019 and 2020 and then followed up for 8 weeks. Results: A total of 10 patients were included in this study, with a mean age of 24 months; 50% were female. BT was able to reduce the inflammatory process in the liver caused by the continuous use of parenteral nutrition; enteral caloric intake increased from 25.32 kcal/kg/day to 72.94 kcal/kg/day, but it was insufficient to improve their nutritional status. Conclusions: BT is a safe and effective alternative in intestinal rehabilitation in patients with SBS to stimulate trophism and intestinal functionality, allowing a progression of enteral feeding and a decrease in the hepatic inflammatory process that occurs in these patients with prolonged parenteral nutrition.